Exercise in a hot environment influences plasma anti-inflammatory and antioxidant status in well-trained athletes - Sureda, A.; Mestre-Alfaro, A.; Banquells, M.; Riera, J.; Drobnic, F.; Camps, J.; Joven, J.; Tur, J.. A.; Pons, A. (Journal of Thermal Biology, 2015)
Exercise in thermally stressful environmental conditions can enhance oxidative stress. We sought to measure the plasma antioxidant defenses and cytokine response together with oxidative damage post-exercise in a temperate versus a hot environment. The plasma concentrations of vasoactive endothelin-1 and vascular angiogenic growth factor were also evaluated. Male athletes (n=9) volunteered to participate. The athletes randomly performed two bouts of treadmill exercise of 45min at 75-80% of maximal oxygen uptake in a climatic-controlled chamber under two different conditions: temperate environment (10-12°C, 40-55% humidity) and hot, humid environment (30-32°C, 75-78% humidity). Venous blood samples were obtained immediately pre- and post-bout and on recovery after 2h. Serum glucose, malondialdehyde and lactate concentrations were significantly increased post-exercise in hot but maintained in the temperate environment; these post-exercise values were significantly higher after exercise in hot than in temperate. Urinary 8-hydroxy-2'-deoxyguanosine concentration, plasma phosphocreatine kinase and catalase activities, creatinine and monocyte chemoattractant protein-1, and interleukin-6 significantly increased post-exercise in hot but maintained in temperate environment. The post-exercise circulating values of antioxidant enzyme paraoxonase-1 and endothelin were significantly higher in the hot than in temperate environment. Exercise in a hot and humid environment resulted in mild hyperthermia with elevated perceived exertion and thermal stress. Hyperthermic environment induced hyperglycemia, lactatecidemia and more cellular and oxidative damage than exercise in a temperate environment but also induced a post-exercise antioxidant and anti-inflammatory response in plasma. These results suggest that environmental temperature needs to be taken into account when evaluating exercise-related oxidative stress and inflammation.